2005
DOI: 10.1063/1.1850751
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic analysis of liquid films dip-coated onto chemically micropatterned surfaces

Abstract: The dip coating of chemically heterogeneous surfaces is a useful technique for attaining selective material deposition. For the case of vertical, wetting stripes surrounded by nonwetting regions, experiments have demonstrated that the thickness of the entrained film on the stripes is significantly different than on homogeneous surfaces because of the lateral confinement of the liquid. In the present work, the asymptotic matching of equations based on lubrication theory is used to determine the film thickness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…12,19 This linkage of the capillary ridge to instability is also supported by results from recent studies of liquid film dynamics on chemically patterned substrates. Liquid confinement to a narrow wetting strip induces a significant transverse curvature of the free surface, 20,21 which suppresses the capillary ridge and fingering instability. 22,23 By contrast, Kalliadasis and Homsy 24 recently found that the stationary capillary ridge near an isolated topographical step-down is asymptotically stable to transverse perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…12,19 This linkage of the capillary ridge to instability is also supported by results from recent studies of liquid film dynamics on chemically patterned substrates. Liquid confinement to a narrow wetting strip induces a significant transverse curvature of the free surface, 20,21 which suppresses the capillary ridge and fingering instability. 22,23 By contrast, Kalliadasis and Homsy 24 recently found that the stationary capillary ridge near an isolated topographical step-down is asymptotically stable to transverse perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…The mean curvature in the static meniscus region therefore reduces to 2 = 0, and the exact meniscus profile need not be determined explicitly. 19 Evaluating 2 along the centerline of the stripe ͑y =0͒ and noting that the free surface must be symmetric ͑and that h x → 0 at the top of the static meniscus to match the dynamic meniscus͒ reveals that h xx + h yy → 0 is the desired limiting behavior at the top of the static meniscus to which the solution in the dynamic meniscus should be matched. For the surfactant concentration, ⌫ → ⌫ 0 .…”
Section: Static Meniscusmentioning
confidence: 99%
“…Also, in this static meniscus region, for BoӶ 1, the liquid-vapor interface within several stripe widths of the wall is a minimal surface with zero mean curvature ͑2 =0͒. 19 In order to neglect gravity in Eq. ͑23͒, it was required that BoӶ Ca 1/3 .…”
Section: Static Meniscusmentioning
confidence: 99%
See 2 more Smart Citations